The contemplative intelligence in the Quran and Sunnah and its role in knowlledge acquisition - Salim, Ssuna; Abdullah, Syahrul Faizaz (AESS Publications, 2014)
The aim of this study is to analyze the contemplative intelligence, the ability of the individual to essentially possess a knowledge that relates the knower to higher modes of being.This knowledge is identified with shuhud (vision) and ta’ammul as one of the most important aspects of an Islamic personality in the process of knowledge acquisition which if neglected will negatively affect the process knowledge acquisition.The descriptive analytical synthetic descriptive approach is used which is mainly interpretative in the form of textual commentary.The study defines and critically analyzes Quranic and Prophetic traditions in relation to what contemplative intelligence is and its relation to knowledge acquisition.The study explains means and ways how the contemplative intelligence should be developed and what is its role in creating God-conscious personalities which will get fully closer to Allah the Almighty in all their endeavors in order to effectively acquire beneficial knowledge.The study concludes by viewing the contemplative intelligence as an indispensable aspect of contemporary Muslims.The study advocates that all Muslim institutions of learning, parents, teachers, preachers and all levels of Muslim communities must have a clear understanding or at least an exposure of this aspect, since it acts as a drive to the soul traveling on the path of God in this life and the life hereafter.